Single Frame Resection of Compact Digital Cameras for UAV Imagery - Martinus Edwin Tjahjadi; Fourry Handoko (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Recently, UAVs (Unmanned Aerial Vehicles) gaina wider acceptance from many disciplines. One major applicationis for monitoring and mapping. Flying beyond eye sightautonomously and collecting data over large areas are theirobvious advantages. To support a large scale urban city mapping,we have developed a UAV system which can carry a compactdigital camera as well as a navigational grade of a GlobalPositioning System (GPS) board mounted on the vehicle.Unfortunately, such a navigational system fails to providesufficient accuracy required to process images become a largescale map. Ubiquitous digital compact cameras, despite their lowcost benefits, are widely known to suffer instabilities in theirinternal lenses and electronics imaging system. Hence thesecameras are less suitable for mapping related purposes. However,this paper presents a photogrammetric technique to preciselydetermine intrinsic and extrinsic camera parameters ofphotographed images provided that sufficient numbers ofsurveyed control points are available. A rigorous Mathematicalmodel is derived to compute each image position with respect tothe imaging coordinate system as well as a location of theprincipal point of an image sensor and the focal length of thecamera. An iterative Gaussian-Newton least squares adjustmentmethod is utilized to compute those parameters. Finally, surveyeddata are processed and elaborated to justify the mathematicalmodels.